Low-fluoride gels supplemented with nano-sized sodium trimetaphosphate reduce dentin erosive wear in vitro - Díaz-Fabregat, Beatriz [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Ramírez-Carmona, Wilmer [UNESP]; Capalbo, Letícia Cabrera [UNESP]; Báez-Quintero, Liliana Carolina [UNESP]; Wiegand, Annette; Monteiro, Douglas Roberto [UNESP]; Pessan, Juliano Pelim [UNESP] (Elsevier, 2024)
Objective: The study assessed the effect of low-fluoride gels supplemented with micrometric or nano-sized sodium trimetaphosphate (TMP) on dentin erosive wear in vitro. Design: Bovine dentin blocks (n = 154) were selected by surface microhardness and randomly allocated into seven groups (n = 22/group), according to the gels: Placebo; 4500 ppm F (4500F); 9000 ppm F (9000F); 5% TMP microparticulate plus 4500F (5TMPm+4500F); 2.5% TMP nanoparticulate plus 4500 F (2.5TMPn+4500F); 5% TMP nanoparticulate plus 4500F (5TMPn+4500F); and 12,300 ppm F acid gel (APF). All blocks were treated only once for 60 s and cyclically eroded (ERO, citric acid, 4 × 90 s/day) or eroded and brushed (4 × 15 s/day, five strokes/s, ERO+ABR) over five days (each subgroup n = 11). Dentin wear and integrated hardness loss in depth (ΔKHN) were determined, and the data were submitted to two-way ANOVA, followed by Tukey's test, and Spearman's correlation (p < 0.05). Results: For ERO, all gels containing 4500F supplemented with TMP significantly reduced dentin wear compared with their counterpart without TMP, reaching values similar to 9000F. For ERO+ABR, 5TMPn+ 4500F gel led to significantly lower wear than all its counterparts, reaching values similar to 9000F and APF. As for ΔKHN, all gels containing TMP promoted superior protective effects compared with 4500F, reaching values similar to 9000F and APF under both challenges. A positive correlation between dentin wear and mineral content in depth was verified. Conclusions: Gels containing 4500F supplemented with TMP significantly reduced dentin erosive wear compared with pure 4500F, with additional benefit from the use of nanoparticles.
Keywords: Dentin; Nanoparticles; Polyphosphates; Sodium fluoride; Tooth erosion